2020
DOI: 10.1101/2020.01.28.921841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding the contents of consciousness from prefrontal ensembles

Abstract: Multiple theories attribute to the primate prefrontal cortex a critical role in conscious perception. However, opposing views caution that prefrontal activity could reflect other cognitive variables during paradigms investigating consciousness, such as decision-making, monitoring and motor reports. To resolve this ongoing debate, we recorded from prefrontal ensembles of macaque monkeys during a no-report paradigm of binocular rivalry that instigates internally driven transitions in conscious perception. We cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 86 publications
4
37
0
Order By: Relevance
“…Overall, to the best of our knowledge, the current study describes the representation of conscious and subconscious stimuli in IT cells in the most confound-free way to date. Our study complements a study conducted in parallel by Kapoor et al, 2020 that found modulations by conscious percept in prefrontal cortex using a different no-report paradigm based on optokinetic nystagmus.…”
Section: Discussionsupporting
confidence: 73%
“…Overall, to the best of our knowledge, the current study describes the representation of conscious and subconscious stimuli in IT cells in the most confound-free way to date. Our study complements a study conducted in parallel by Kapoor et al, 2020 that found modulations by conscious percept in prefrontal cortex using a different no-report paradigm based on optokinetic nystagmus.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, to the best of our knowledge, this study shows representations of the conscious percept in IT cortex in the most confound-free way to date. Our study complements a study conducted in parallel by Kapoor et al (2020) that found modulations by conscious percept in prefrontal cortex using a different no-report paradigm based on optokinetic nystagmus.…”
Section: Discussionsupporting
confidence: 73%
“…Yet, previous research has repeatedly shown that prefrontal cortex may indeed represent the contents of conscious experience 51,52 . Intersecting computational models of dynamic conflict-accumulation 14 with no-report paradigms of bistable perception will enable future research to test whether the contents of conscious experience are represented 53 or multiplexed 54 within the neural correlates of perceptual conflict, creating exciting new opportunities to better understand the role of prefrontal cortex in consciousness.…”
Section: Discussionmentioning
confidence: 99%